Pragmatic Program of Lecture Text - Q. Yang (Научный диалог)
The issue of subjective-modal component of the content, or pragmatic program of the lecture text is considered. Attention is paid to components which are defined by the involvement of the subject of the text (the lecturer) in two different components of verbal communication: the objective content of the text and the addressee of the speech. The question is raised about modal focusing on separate sections of the objectively-logical text as short inclusions called pragmatically important components of the text. The novelty of the research is seen in the integrated communicative approach to the analysis of subjective modal content of the scientific-educational text. The urgency of the problem is linked with the development of methods of linguistic description of pragmatically important components of the text. The definitions for pragmatic programmes of the text and its components are given, the review of the scientific literature on the subject is made. The author dwells on certain varieties of pragmatically important components: stylistic figures and techniques of dialogisation. Classification of their functions is presented. It is proved that the application of the considered methods modal focusing is typical within the genre of the lecture. Each technique is characterized by qualitative characteristics: anaphora forms a meaningful text fragments and provides a logical relationship of the fragments; asyndeton is a means of characterization of a subject; techniques of dialogisation contribute to the creation of comfortable communication in the lecture hall. A pragmatic program in general contributes to the solution of didactic tasks of the lecture text.